Morphological changes in the brain in severe traumatic brain injury aggravated by alcohol intoxication - Mardanov Jamshid Jaxongirovich (Genius Journals, 2023)
All components of the human dura mater and its vascular system in traumatic brain injury were studied: all layers of the dura mater, vessels of the arterial and venous type, the nature of branching, their condition. Pathological processes in the form of hyalinosis and fibrosis of the layers of the vascular wall under the influence of alcohol cause bifurcationhemodynamic insufficiency, causing protrusion of the vascular wall. In this case, we can talk about alcohol-dependent bifurcation-hemodynamic insufficiency
Keywords: dura mater; alcohol intoxication; meningeal bleeding